Metabolic reconstruction of the genome of candidate Desulfatiglans TRIP_1 and identification of key candidate enzymes for anaerobic phenanthrene degradation. (7th February 2019) - Kraiselburd, Ivana; Brüls, Thomas; Heilmann, Geronimo; Kaschani, Farnusch; Kaiser, Markus; Meckenstock, Rainer U.
Summary: Polycyclic aromatic hydrocarbons (PAHs) are widely distributed pollutants. As oxygen is rapidly depleted in water‐saturated PAH‐contaminated sites, anaerobic microorganisms are crucial for their consumption. Here, we report the metabolic pathway for anaerobic degradation of phenanthrene by a sulfate‐reducing enrichment culture (TRIP) obtained from a natural asphalt lake. The dominant organism of this culture belongs to the Desulfobacteraceae family of Deltaproteobacteria and genome‐resolved metagenomics led to the reconstruction of its genome along with a handful of genomes from lower abundance bacteria. Proteogenomic analyses confirmed metabolic capabilities for dissimilatory sulfate reduction and indicated the presence of the Embden‐Meyerhof‐Parnas pathway, a complete tricarboxylic acid cycle as well as a complete Wood‐Ljungdahl pathway. Genes encoding enzymes putatively involved in the degradation of phenanthrene were identified. This includes two gene clusters encoding a multisubunit carboxylase complex likely involved in the activation of phenanthrene, as well as genes encoding reductases potentially involved in subsequent ring dearomatization and reduction steps. The predicted metabolic pathways were corroborated by transcriptome and proteome analyses, and provide the first insights into the metabolic pathway responsible for the anaerobic degradation of three‐ringed PAHs.